Pengaruh Moralitas Individu, Komitmen Organisasi, Kultur Organisasi, Dan Gaya Kepemimpinan Terhadap Good Corporate Governance Pada Lpd Se-Kabupaten Buleleng - yumia, sania; Sujana, Edy (Universitas Pendidikan Ganesha, 2021)
This research aims to determine the effect of individual morality, organizational commitment, organizational culture, and leadership style on good corporate governance in LPDs throughout Buleleng Regency. The population of this research is all employees who work in LPD in Buleleng Regency totaling 818 people, the sample technique used is purposive sampling. The number of samples in this research are 96 respondents. The data analysis technique in this research is quantitative using multiple linear regression analysis. The results of this research indicate that are (1) individual morality has a positive and significant effect on good corporate governance, (2) organizational commitment has a positive and significant effect on good corporate governance, (3) organizational culture has a positive and significant effect on good corporate governance, (4) Leadership Style has a positive and significant effect on good corporate governance.Â Â